1999
DOI: 10.1530/jrf.0.1170291
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of donor primordial germ cells into functional gametes in the gonads of mixed-sex germline chimaeric chickens produced by transfer of primordial germ cells isolated from embryonic blood

Abstract: This study was carried out to elucidate whether primordial germ cells, obtained from embryonic blood and transferred into partially sterilized male and female recipient embryos, could differentiate into functional gametes and give rise to viable offspring. Manipulated embryos were cultured until hatching and the chicks were raised until maturity, when they were mated. When the sex of the donor primordial germ cells and the recipient embryo was the same, 15 out of 22 male chimaeric chickens (68.2%) and 10 out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 0 publications
2
61
1
Order By: Relevance
“…Choi et al (2) reported 12.5-82.6% (49.0% on average) germ-line transmission by transferring mixed PGCs, and Macdonald et al (3) estimated that the frequency of donor-derived sperm was 1-30% in the semen of recipient roosters, even though the endogenous PGCs of recipient embryos were depleted by irradiation. The frequencies in these previous reports were similar to the rates of germ-line transmission obtained from chimeras after the transfer of freshly isolated or short-term cultured PGCs (15,16). However, in the test-cross analysis of the present study, the efficiency of germ-line transmission of donor PGCs ranged from 90.4 to 98.9% in six donor PGC-transplanted founders (437 donor-derived chicks of 459 total hatched chicks, 95.2%).…”
Section: Characterizations After Transfection and G418-selection Of Csupporting
confidence: 87%
See 1 more Smart Citation
“…Choi et al (2) reported 12.5-82.6% (49.0% on average) germ-line transmission by transferring mixed PGCs, and Macdonald et al (3) estimated that the frequency of donor-derived sperm was 1-30% in the semen of recipient roosters, even though the endogenous PGCs of recipient embryos were depleted by irradiation. The frequencies in these previous reports were similar to the rates of germ-line transmission obtained from chimeras after the transfer of freshly isolated or short-term cultured PGCs (15,16). However, in the test-cross analysis of the present study, the efficiency of germ-line transmission of donor PGCs ranged from 90.4 to 98.9% in six donor PGC-transplanted founders (437 donor-derived chicks of 459 total hatched chicks, 95.2%).…”
Section: Characterizations After Transfection and G418-selection Of Csupporting
confidence: 87%
“…S2). Only male SNUhp26 PGC-transplanted roosters were test-crossed because the reverse-sexed chimeras failed to produce donor-derived offspring and the efficiency of germ-line transmission was quiet low compared with those of the single-sex chimeras of previous reports (1,3,15). Among the donor PGC-derived progenies, the transgenic chicks could be easily identified with a fluorescent excitation lamp and the detection filters because of strong GFP expression in all transgenic chick tissues, including the beak, feather pulp, feet, and muscle ( Fig.…”
Section: Characterizations After Transfection and G418-selection Of Cmentioning
confidence: 99%
“…Isolation of PGCs from early stage embryos and transferring to recipient embryos can produce same-sex and mixed-sex germline chimeric chickens. Naito et al (1999Naito et al ( , 2001) produced same-sex and mixed-sex germline chimeric chickens by transfer of the stage X blastodermal cells containing PGCs (or their precursor cells) and PGCs isolated from the blood of 2. 5-day incubated embryos.…”
Section: Germline Chimeric Chickensmentioning
confidence: 99%
“…Therefore, manipulation of germline cells is currently considered to be the more useful method for gene transfer into chickens (Naito et al, 2010). Since primordial germ cells (PGCs) are progenitor cells of ova and spermatozoa, germline chimaeric chickens can be produced by transfer of PGCs between embryos (Tajima et al, 1993;Naito et al, 1994aNaito et al, , 1994bNaito et al, , 1998Naito et al, , 1999). An in vitro culture of PGCs makes it possible to incorporate stably exogenous genes into PGCs.…”
Section: Introductionmentioning
confidence: 99%